HLA, Immune Response, and Susceptibility to COVID-19 - Tavasolian, Fataneh; Rashidi, Mohsen; Hatam, Gholam Reza; Jeddi, Marjan; Hosseini, Ahmad Zavaran; Mosawi, Sayed Hussain; Abdollahi, Elham; Inman, Robert D. (Frontiers in Immunology, 2021)
The severe acute respiratory syndrome caused by Coronavirus 2 (SARS-CoV-2) that appeared in December 2019 has precipitated the global pandemic Coronavirus Disease 2019 (COVID-19). However, in many parts of Africa fewer than expected cases of COVID-19, with lower rates of mortality, have been reported. Individual human leukocyte antigen (HLA) alleles can affect both the susceptibility and the severity of viral infections. In the case of COVID-19 such an analysis may contribute to identifying individuals at higher risk of the disease and the epidemiological level to understanding the differences between countries in the epidemic patterns. It is also recognized that first antigen exposure influences the consequence of subsequent exposure. We thus propose a theory incorporating HLA antigens, the “original antigenic sin (OAS)” effect, and presentation of viral peptides which could explain with differential susceptibility or resistance to SARS-CoV-2 infections.